2021
DOI: 10.1002/batt.202100319
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked Polymer‐Brush Electrolytes: An Approach to Safe All‐Solid‐State Lithium Metal Batteries at Room Temperature

Abstract: Electric vehicles, intelligent machines, and portable electronics in our daily lives are placing insatiable demand on safe and powerful battery materials that can function at room temperature. Herein, we report an ultrathin and robust solid-state electrolyte with crosslinked polymer-brush architecture. On one hand, the highly mobile polymer brushes with a moderate side chain length enable efficient cation solvation and fast ion transport, offering room-temperature ionic conductivity as high as 0.23 mS cm À 1 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…10 10 s –1 ), resulting in unqualified ionic conductivity for practical battery applications. To further improve the ionic conductivity of PEO-based SPEs, various molecular engineering strategies are proposed, including grafting brush polymers, , block copolymers, cross-linking polymers, nanoparticle incorporation, and others. , …”
Section: Introductionmentioning
confidence: 99%
“…10 10 s –1 ), resulting in unqualified ionic conductivity for practical battery applications. To further improve the ionic conductivity of PEO-based SPEs, various molecular engineering strategies are proposed, including grafting brush polymers, , block copolymers, cross-linking polymers, nanoparticle incorporation, and others. , …”
Section: Introductionmentioning
confidence: 99%
“…The design and synthesis of novel polymer matrices have shown to be effective for improving the performance of SHEs. Various approaches have been explored to enhance the ionic conductivity of polymer electrolytes, including the use of hyperbranching, [188][189][190][191] brushing, [192][193][194][195] star-shape, [196][197][198][199][200] comb-like, [201][202][203][204] cross-linked structures, [205][206][207][208][209][210][211] blending, [212][213][214] plasticizers, 215,216 and polymers in salts. Yamamoto's group conducted research on hyperbranched poly(bistriethylene glycol benzoate) (Fig.…”
Section: Ionic Conductivitymentioning
confidence: 99%
“…It was indicated that the SPE had no melting point and was entirely amorphous, which was advantageous for improving ionic conductivity. The SPE demonstrated a high ionic conductivity of 2.35×10 −4 S cm −1 at room temperature with no short circuit for a period of 2000 h, and a broad electrochemical window of about 4.63 V. Ji et al [107] . designed a brush‐like cross‐linked polymer separator with strong dendrite resistance and thermal stability of inorganic particles.…”
Section: Modification Technology Of High‐temperature‐resistant Separatormentioning
confidence: 99%